COMMUNITY EMPOWERMENT THROUGH THE UTILIZATION OF PLASTIC WASTE INTO ECOBRICKS AS AN EFFORT TO REDUCE PLASTIC WASTE IN SIKALANG VILLAGE, SAWAHLUNTO, WEST SUMATRA - Linda Marni; Siti Hardianti Harahap; Aines Putri Burma; Annisa Sahra; Muhammad Ikhwan; M. Riski Wahyudi (PT. Jurnal Center Indonesia Publisher, 2025)
This community service research focuses on empowering the Sikalang Village community in household plastic waste management through ecobrick creation, serving as a concrete solution to reduce waste and preserve the ecosystem. Conducted over 30 days (June 17 - July 17, 2025) using a Participatory Action Research approach, the activities encompassed planning, door-to-door socialization, plastic waste collection and compaction into bottles, and the assembly of ecobricks into the